Kinematic analysis of the ball impact in female soccer players - Sakaomoto, K.; Geisler, G.; Nakayama, M.; Asai, T. (Procedia Engineering, 2011)
In recent years, the number of female soccer players has been increasing worldwide; however, few studies have investigated the kicking technique of female players. Accordingly, this study used 3 high-speed video cameras (1000 fps) to compare the ball velocity, foot velocity, repulsion ratio, and angular displacement at ball impact of the instep kick and inside kick in female and male soccer players to identify the mechanical and technical characteristics of female players at ball impact. For both kicks, the ball velocity, foot velocity immediately prior to impact, and average repulsion ratio were smaller for the female players than for the male players. For both males and females, there tended to be a lower repulsion ratio the further the impact point was from the centre of gravity of the foot. The mechanical properties of the ankle joint in female players during the instep kick may involve slightly lower dynamic stiffness than that of the male players. In addition, the lower dynamic stiffness of the ankle joint in female players is believed to have a comparatively greater effect on the instep kick, suggesting that impacting the ball with the centre of gravity of the foot is even more important.